Atopic Dermatitis-Like Skin Lesions Reduced by Topical Application and Intraperitoneal Injection of Hirsutenone in NC/Nga Mice - Mi Sook Jeong; Sun Eun Choi; Ji Young Kim; Jung Shim Kim; Eun Joo Kim; Kwan Hee Park; Do Ik Lee; Seong Soo Joo; Chung Soo Lee; Hyoweon Bang; Mi-Kyung Lee; Young Wook Choi; et al. (Clinical and Developmental Immunology)
Atopic dermatitis (AD) is a common inflammatory skin disease. The increasing prevalence and severity of AD have prompted the developments of safer, more effective drugs. Although topical corticosteroids have been used as first line therapy for AD, their potential side effects limit their clinical applications. To investigate the effect of hirsutenone (HIR), a diarylheptanoid compound, on AD-like skin lesions and other factors related to immune response is the aim of this paper Th2-related cytokines (IL-4, IL-5, IL-13), eosinophil, IgE inflammatory factors (COX-2, iNOS) levels were reduced in blood, lymphocytes, and tissue after HIR treatment. These results suggest that HIR might be an effective treatment for AD.